Novel multi-virus rapid respiratory microbiological point-of-care testing in primary care: a mixed-methods feasibility evaluation. (4th March 2021) - Khalid, Tanzeela Y; Duncan, Lorna J; Thornton, Hannah V; Lasseter, Gemma; Muir, Peter; Toney, Zara Abigail; Hay, Alastair D
Abstract: Background and Objectives: Rapid multi-viral respiratory microbiological point-of-care tests (POCTs) have not been evaluated in UK primary care. The aim of this study was to evaluate the use of a multi-viral microbiological POCT for suspected respiratory tract infections (RTIs). Methods: In this observational, mixed-methods feasibility study practices were provided with a POCT machine for any patient aged ≥3 months with suspected RTI. Dual throat/nose swabs tested for 17 respiratory viruses and three atypical bacteria, 65 minutes per sample. Results: Twenty clinicians recruited 93 patients (estimated 1:3 of all RTI cases). Patient's median age was 29, 57% female, and 44% with co-morbidities. Pre-test diagnoses: upper RTI (48%); lower RTI (30%); viral/influenza-like illness (18%); other (4%). Median set-up time was 2.72 minutes, with 72% swabs processed <4 hours, 90% <24 hours. Tests detected ≥1 virus in 58%, no pathogen 37% and atypical bacteria 2% (3% inconclusive). Antibiotics were prescribed pre-test to 35% of patients with no pathogen detected and 25% with a virus. Post-test diagnoses changed in 20%, and diagnostic certainty increased ( P = 0.02), more so when the test was positive rather than negative ( P < 0.001). Clinicians predicted decreased antibiotic benefit post-test ( P = 0.02). Interviews revealed the POCT has clear potential, was easy to use and well-liked, but limited by time-to-result and the absence of testing for typical respiratory bacteria. Conclusions: This POCT was acceptable and appeared to influence clinical reasoning. Clinicians wanted faster time-to-results and more information about bacteria. Randomized trials are needed to understand the safety, efficacy and patient perceptions of these POCTs. Lay Summary: The UK government has called for the introduction of rapid diagnostics to curb overuse of antibiotics for common infections. Multi-viral respiratory 'point-of-care' tests (POCTs) are available but have not been used in UK primary care before. These POCTs use samples from the nose or back of the throat and give results quickly, to see if viruses or bacteria are there. In this study, four GP practices were given POCT machines for 6 weeks to see how they were used. Of the 93 patient samples tested, 3% were inconclusive, 37% tested negative, 58% had at least one virus and only 2% had a bacterial infection. Clinicians were more certain of patient diagnoses after testing especially when a virus or bacterium was detected and they were also less likely to predict the patient would benefit from antibiotics. Clinical diagnoses changed in 20% of patients after testing but less than 10% were contacted to change their treatment plan. During interviews, clinicians revealed they liked the test finding it easy-to-use but wanted faster time-to-results and testing for more bacteria. Clinical trials are needed to see if these POCTs can safely and cost-effectively reduce antibiotic prescribing in primary care.